2013
DOI: 10.2174/138161213805289309
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on New Synthetic Curcumin Analogs and their Potential Anticancer Properties

Abstract: Curcumin is the active component of dried rhizome of Curcuma longa, a perennial herb belonging to ginger family, cultivated extensively in south and southeastern tropical Asia. It is widely consumed in the Indian subcontinent, south Asia and Japan in traditional food recipes. Extensive research over last few decades has shown that curcumin is a potent anti-inflammatory agent with powerful therapeutic potential against a variety of cancers. It suppresses proliferation and metastasis of human tumors through regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 117 publications
0
62
0
Order By: Relevance
“…Many of the reported analogues of curcumin are either arylvinylketones or bis-(arylvinyl)ketones. The curcumin analogues that did not adhere to the 7-atom linker rule kept good to excellent Pgp inhibition activities [30]. …”
Section: Resultsmentioning
confidence: 99%
“…Many of the reported analogues of curcumin are either arylvinylketones or bis-(arylvinyl)ketones. The curcumin analogues that did not adhere to the 7-atom linker rule kept good to excellent Pgp inhibition activities [30]. …”
Section: Resultsmentioning
confidence: 99%
“…As a result, several strategies have been developed to improve its bioavailability, including the development of curcumin predrugs and structural analogues, blocking the metabolic pathways of curcumin using adjuvants, increasing the solubility of curcumin by forming phospholipid complexes or PEGylation, and promoting absorption using a delivery system involving carrier vehicles, such as polymer nanoparticles, liposomes, phytosomes and surfactant micelles (Anand et al, 2008;Vyas et al, 2013). It is noteworthy that the addition of adjuvant piperine, an inhibitor of glucuronidation of curcumin, has been demonstrated to increase 150% bioavailability of curcumin in rats and 2000% in man (Anand et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…However, low bioavailability of these agents limits their therapeutic application, and the concentrations needed for retardation of tumor growth in rodents greatly exceed doses compatible with human use [2729]. The utilization of the ability of polyphenols to synergistically enhance anticancer effects of one another in different models [3033] has been suggested, among other approaches [28, 34], to improve their bioactivity in vivo . Using this combination strategy, we have previously shown that CUR and another polyphenol, carnosic acid (CA), combined at potentially bioavailable non-cytotoxic concentrations of each agent robustly triggered apoptosis in KG-1a and HL60 AML cells [35].…”
Section: Introductionmentioning
confidence: 99%